Role-Playing Games for Language Enhancement: A Linguistic Study of Baldur’s Gate 3 - Felipe Cacho Corpuz (Universitas Pendidikan Ganesha, 2024)
This study delves into the linguistic advantages presented by role-playing games (RPGs), with a particular focus on Baldur’s Gate 3. Through a thorough examination involving content analysis and sixty hours of personal gameplay observation by the researcher, this research explores the linguistic components embedded within the game that contribute to skill improvement in areas such as vocabulary, grammar, comprehension, and pronunciation. The findings highlight notable enhancements across all linguistic aspects within the game environment. Exposure to a diverse range of lexical elements, including character names and quest-related terms, leads to significant vocabulary enrichment. Moreover, the navigation through the intricacies of non-player character (NPC) dialogues significantly enhances language interpretation abilities. The grammatically rich dialogues and precise pronunciation showcased through character voice acting further contribute to heightened grammatical proficiency and especially improved language articulation. Ultimately, the study underscores the very game, Baldur’s Gate 3, as an effective tool for language acquisition, providing the researcher and the potential players with a multifaceted approach to honing their vocabulary, grammar, comprehension, and pronunciation skills. By revealing the specific linguistic features within the game and their corresponding benefits to the aforementioned linguistic skills, this research offers a comprehensive roadmap for individuals interested in utilizing role-playing games for language enhancement purposes.